Restorative Justice Approach in Traffic Crime Law Enforcement - Jabida Sopamena (International Journal of Law and Society, 2024)
This research explores the application of restorative justice, focusing on traffic cases resulting in fatalities, as outlined in Chapter XIX of the KUHP, which addresses crimes against the body. The study examines instances where traffic accidents caused deaths but were resolved through restorative justice practices. The findings indicate that within the National Police institution, the application of restorative justice in traffic cases is governed by both general and special conditions. These conditions are often conflicting, as general regulations typically reject restorative justice if a victim dies, yet special conditions allow for the possibility of resolving such cases at the investigation and inquiry levels. Similarly, at the Prosecutor's Office, the study revealed that the process of halting prosecution is generally not permissible for cases carrying sentences of over five years. However, in specific instances, exceptions are made, even though the Prosecutor's Office does not specifically address traffic crimes but regulates them under general provisions. This leads to an asynchronous approach to case resolution through restorative justice. The author concludes that there is a critical need for a dedicated law on Restorative Justice to ensure regulatory synchronization, thus providing clear and consistent guidelines for the application of restorative justice in traffic cases resulting in fatalities.